Current conception about the pathogenesis and intensive care of severe COVID-19 (review) - Georgiyants, Marine; Korsunov, Volodymyr; Dubrov, Sergii; Loskutov, Oleg; Bohuslavska, Nataliia; Nikonov, Vadim; Cherkashyna, Lidiya; Oparin, Oleksiy; Nartov, Pavel; Holianishchev, Maksym (ScienceRise: Medical Science, 2021)
The aim of the research. The aim of this work was to summarize the scientific literature data on the pathogenesis and intensive care of the severe course of coronavirus infection. Materials and methods. Databases such as PubMed, Google Scholar, Scopus and Web Of Science 2020-2021 were used for literary searches. Results. An intense inflammatory response against the SARS-CoV-2 virus in COVID-19 patients causes a cytokine storm and hypercoagulability with the development of acute respiratory distress syndrome (ARDS) and multiple organ failure. Approximately 17 % to 35 % of hospitalized patients with COVID-19 are treated in the intensive care unit, most often due to hypoxemic respiratory failure and the development of ARDS, and between 29 % and 91 % of patients in intensive care units require invasive ventilation. In addition to acute respiratory failure, hospitalized patients may have acute renal failure (9 %), liver dysfunction (19 %), coagulation disorders (10 %–25 %), and septic shock (6 %). More than 75 % of hospitalized patients require additional oxygen therapy. Respiratory support could vary from the need for oxygen supplementation through a nasal catheter to invasive ventilation or extracorporeal membrane oxygenation in patients with the most severe ARDS. The uncontrolled inflammation and coagulation seen in COVID-19 patients is similar to multifactorial ARDS, where a plethora of evidence has demonstrated the ability of long-term corticosteroid therapy (CST) to reduce inflammation-coagulation-fibroproliferation and accelerate recovery. With regard to the assessment of the benefits of therapeutic anticoagulation in patients with elevated D-dimer, the question has not yet been finally resolved, and research devoted to this is still ongoing. Conclusions. The approaches to respiratory, anticoagulant, anti-inflammatory therapy in critically ill patients with COVID-19 require further research to determine the optimal treatment tactics